Subjective memory complaints among patients on sick leave are associated with symptoms of fatigue and anxiety - Aasvik, Julie K.; Woodhouse, Astrid; Børsting Jacobsen, Henrik; Borchgrevink, Petter C.; Stiles, Tore C.; Landrø, Nils Inge (Frontiers in Psychology, 2015)
Abstract: Objective: The aim of this study was to identify symptoms associated with subjective memory complaints among subjects who are currently on sick leave due to symptoms of chronic pain, fatigue, depression, anxiety and insomnia. Methods: This was a cross-sectional study, subjects (n = 167) who were currently on sick leave were asked to complete an extensive survey consisting of the following: items addressing their sociodemographics, one item from the SF-8 health survey measuring pain, Chalder Fatigue Questionnaire, Hospital Anxiety and Depression Scale, Insomnia Severity Index and Everyday Memory Questionnaire – Revised. General linear modeling (GLM) was used to analyze variables associated with SMCs. Results: Symptoms of fatigue (p-value <= 0.001) and anxiety (p-value = 0.001) were uniquely and significantly associated with perceived memory failures. The associations with symptoms of pain, depression and insomnia were not statistically significant. Conclusions: Subjective memory complaints should be recognized as part of the complex symptomatology among patients who report multiple symptoms, especially in cases of fatigue and anxiety. Self-report questionnaires measuring perceived memory failures may be a quick and easy way to incorporate and extend this knowledge into clinical practice.